Transcriptional changes and preservation of bone mass in hibernating black bears - Anna V. Goropashnaya (Nature Portfolio, 2021)
Abstract Physical inactivity leads to losses of bone mass and strength in most mammalian species. In contrast, hibernating bears show no bone loss over the prolonged periods (4–6 months) of immobility during winter, which suggests that they have adaptive mechanisms to preserve bone mass. To identify transcriptional changes that underlie molecular mechanisms preventing disuse osteoporosis, we conducted a large-scale gene expression screening in the trabecular bone and bone marrow, comparing hibernating and summer active bears through sequencing of the transcriptome. Gene set enrichment analysis showed a coordinated down-regulation of genes involved in bone resorption, osteoclast differentiation and signaling, and apoptosis during hibernation. These findings are consistent with previous histological findings and likely contribute to the preservation of bone during the immobility of hibernation. In contrast, no significant enrichment indicating directional changes in gene expression was detected in the gene sets of bone formation and osteoblast signaling in hibernating bears. Additionally, we revealed significant and coordinated transcriptional induction of gene sets involved in aerobic energy production including fatty acid beta oxidation, tricarboxylic acid cycle, oxidative phosphorylation, and mitochondrial metabolism. Mitochondrial oxidation was likely up-regulated by transcriptionally induced AMPK/PGC1α pathway, an upstream stimulator of mitochondrial function.